Blockchain Technology: Comprehensive Review and Future Directions - Saurav Singh; Madhu Vaishy (International Journal of Computer Science Languages, 2024)
Blockchain technology has emerged as a transformative power, restructuring sectors by offering increased security, transparency, and decentralization. This research paper serves as a comprehensive examination of blockchain, aiming to dissect its intricate structure, explore its myriad applications, confront existing challenges, and envision future advancements. At its core, the problem addressed herein is the imperative to comprehend the present landscape of blockchain technology, discern its limitations, and chart a course toward innovative solutions. Fundamentally, blockchain operates as a distributed ledger, where transactions are securely and immutably recorded across a network of computers. This foundational structure has facilitated the development of numerous applications spanning diverse sectors, including finance, supply chain management, healthcare, and beyond. Through the utilization of cryptographic principles and agreement mechanisms, blockchain instills trust among users, removing the requirement for intermediaries and promoting increased transactional efficiency. However, despite its transformative potential, blockchain is not devoid of challenges. Scalability remains a pertinent issue, as the throughput of most blockchain networks lags behind traditional payment systems. Additionally, concerns surrounding energy consumption, interoperability, and regulatory uncertainty persist, hindering widespread adoption and integration into existing infrastructures. Nevertheless, the future of blockchain holds promise for continued innovation and evolution. Ongoing research and implementation efforts are focused on scaling solutions like sharding and layer-two protocols, which aim to improve network throughput while maintaining security standards. Additionally, interoperability protocols are being developed to connect different blockchain networks, facilitating smooth communication and cooperation. In conclusion, this research paper endeavors to provide a comprehensive overview of blockchain technology, from its foundational principles to its multifaceted applications and inherent challenges. By critically examining its current state and envisioning future possibilities, it seeks to inspire further exploration and innovation in the realm of decentralized technologies.
Keywords: Blockchain architecture; decentralization; future innovations; scalability challenges; smart contracts